Cost optimization in requirements management for space systems - Katz, Tami E., author; Simske, Steve, advisor; Sega, Ron, committee member; Miller, Erika, committee member; Macdonald, John, committee member (Colorado State University. Libraries, 2021)
When producing complex space systems, the transformation of customer needs into a realized system includes the development of product requirements. The ability to generate and manage the requirements can either enable the overall system development or drive significant cost and schedule impacts. Assessing practices in the industry and publications, it is observed that there is a substantial amount of documented approaches to address requirement development and product verification, but only a limited amount of documented approaches for requirements management. A complex system can have tens of thousands of requirements across multiple levels of development which, if not well managed, can lead to hidden costs associated with missed requirements and product rework. With current space system projects being developed at a rapid pace using more cost constrained approaches such as fixed budgets, an investigation into more efficient processes, such as requirements management, can yield methods to enable successful, cost effective system development. To address the optimal approach of managing requirements for complex space systems, this dissertation assesses current practices for requirements management, evaluates various contributing factors towards optimization of project costs associated with this activity, and proposes an optimized requirements management process to utilize during the development of space systems. Four key areas of process control are identified for requirements management optimization on a project, including utilization of a data focused requirements management approach, development (and review) of requirements using a collaborative software application, ensuring the requirement set is a consolidated with an appropriate amount of requirements for the project, and evaluating when to officially levy requirements on the product developers based on requirement maturation stability. Multiple case studies are presented to evaluate if the proposed requirements management process yields improvement over traditional approaches, including a simulation of the current state and proposed requirements management approaches. Ultimately, usage of the proposed optimized set of processes is demonstrated to be a cost effective approach when compared against traditional processes that may adversely impact the development of new space systems.